1982
DOI: 10.1021/ac00251a017
|View full text |Cite
|
Sign up to set email alerts
|

Matrix and solvent effects on the room-temperature phosphorescence of nitrogen heterocycles

Abstract: noted. Figure 2 shows marked deviation from linearity in the 5-60 ppm range. Uranium concentrations greater than 70 ppm produced decreasing fluorescence intensity readings. Instrument response was linear for uranium, concentrations less than 2.5 ppm. Values greater than 2.5 ppm showed deviations from linearity, indicating that 2.5 ppm uranium is an upper limit to linear response. Solutions with uranium concentrations in the upper ranges of this study would normally require dilution into a linear range to remai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
18
0

Year Published

1984
1984
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 32 publications
(23 reference statements)
0
18
0
Order By: Relevance
“…(9) Nakamura, M. Analyst (London) 1981, 106, 483-487. (10) Nakamura, M. Mlkrochlm. Acta 1983, II, 69-74. (11) Nakamura, M.; Mazuka, T. Anal.…”
Section: Literature Citedmentioning
confidence: 99%
See 1 more Smart Citation
“…(9) Nakamura, M. Analyst (London) 1981, 106, 483-487. (10) Nakamura, M. Mlkrochlm. Acta 1983, II, 69-74. (11) Nakamura, M.; Mazuka, T. Anal.…”
Section: Literature Citedmentioning
confidence: 99%
“…Analogously, strong phosphorescence has been observed from compounds embedded in media which are rigid at room-temperature such as plastics and glasses (1). For compounds adsorbed on cellulose paper and other substrates, it has been proposed that immobilization of the phosphors is accomplished purely with hydrogen bonding interactions between the phosphors and the supports (1,(7)(8)(9)(10)(11). However, Niday and Seybold demonstrated that the addition of selected salts and sugars dramatically enhanced the lifetime of RTF of 2-naphthalenesulfonate on filter paper (12).…”
Section: Literature Citedmentioning
confidence: 99%
“…1982, 54, 2477. (12) Perrin, D. D. "Dissociation Constants of Organic Bases in Aqueous Solution"; Butterworth: London, England, 1965; pp 240, 243, 323.…”
Section: Literature Citedmentioning
confidence: 99%
“…Recent reviews (1, 2) and monographs (3, 4) discuss the theories, techniques, and applications of this approach. The majority of work in this area, thus far, has focused on the optimization of experimental conditions necessary to evoke maximum luminescence intensities and the development of an understanding of the solid-surface interactions leading to the luminescence phenomena (1,(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). The present study considers the use of benzol/]quinoline (B[/]Q) to investigate new interactions of the molecule with silica gel containing a polymeric binder.…”
mentioning
confidence: 99%
“…A relatively large body of information exists on the effects of adsorption of organic molecules on silica surfaces (20-22). Some of the luminescent properties of the probe molecules used in this work, B[/]Q and B[/]QH+, have been detailed elsewhere (7)(8)(9)(10)(11)(12)(13)(14)(23)(24)(25)(26)(27). EXPERIMENTAL…”
mentioning
confidence: 99%